Polyandry and Polygyny in a Social Rodent: An Integrative Perspective Based on Social Organization, Copulations, and Genetics - Hoogland, John L.; Trott, Regina; Keller, Stephen R. (Frontiers in Ecology and Evolution, 2019)
Animal mating systems have fascinated biologists for thousands of years. Accurate descriptions of mating systems are nonetheless elusive, because social organization can be difficult to quantify, documentation of copulations is often challenging, many copulations do not produce offspring, and genetic assignments of parentage are usually expensive. From a 7-year study of colonial white-tailed prairie dogs (Cynomys leucurus) living under natural conditions in Colorado USA, we estimated the frequencies of polyandry (i.e., copulation with >2 males) and polygyny (i.e., copulation with >2 females) from three independent approaches: (1) determination of the number of males and females living in the same territory (social organization); (2) observations of copulations; and (3) genetic assignments of paternity from seven polymorphic microsatellites. For polyandry, behavioral observations and genetics indicate similar overall percentages (27%), but social organization indicates a much lower percentage (2%). For polygyny, behavioral observations indicate the highest overall percentage (84%), then social organization (59%), then genetics (46%). All three approaches show striking annual variation in the frequencies of polyandry and polygyny. Long-term studies that integrate behavioral and genetic insights provide a detailed view of a mating system, but feasibility will depend on ease of capture, visibility of copulations, length of mating season, research objectives, genetic variation, and finances.